2006
DOI: 10.1124/mol.106.025536
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel Shp2 Protein Tyrosine Phosphatase Inhibitor

Abstract: Shp2 is a nonreceptor protein tyrosine phosphatase (PTP) encoded by the PTPN11 gene. It is involved in growth factorinduced activation of mitogen-activated protein (MAP) kinases Erk1 and Erk2 (Erk1/2) and has been implicated in the pathogenicity of the oncogenic bacterium Helicobacter pylori. Moreover, gain-of-function Shp2 mutations have been found in childhood leukemias and Noonan syndrome. Thus, small molecule Shp2 PTP inhibitors are much needed reagents for evaluation of Shp2 as a therapeutic target and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
197
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 268 publications
(202 citation statements)
references
References 37 publications
(45 reference statements)
4
197
1
Order By: Relevance
“…In terms of side effects, Shp2-specific inhibitors may have additional advantages compared with FAK and Akt inhibitors. In the case of the Shp2 inhibitor NSC-87877, it has been shown that the inhibitor preferentially binds Shp2 protein if the gainof-function mutation E76K is present, although the reasons for this are still unclear (37). If PHPS1 also demonstrated preferential binding to mutant Shp2, the possibility of off-target effects would be reduced greatly, but this has not yet been tested.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of side effects, Shp2-specific inhibitors may have additional advantages compared with FAK and Akt inhibitors. In the case of the Shp2 inhibitor NSC-87877, it has been shown that the inhibitor preferentially binds Shp2 protein if the gainof-function mutation E76K is present, although the reasons for this are still unclear (37). If PHPS1 also demonstrated preferential binding to mutant Shp2, the possibility of off-target effects would be reduced greatly, but this has not yet been tested.…”
Section: Discussionmentioning
confidence: 99%
“…34 Figure 4 shows that ProS inhibited VEGF-Ainduced VEGFR2 tyrosine phosphorylation on Tyr 996 but not Tyr 1175 . As shown in Figure 4, the SHP2 inhibitor NSC 87877 25,35 suppressed the ProS inhibitory effect on VEGFA-induced VEGFR2 phosphorylation. The SHP2 inhibitor NSC 87877 reversed the inhibitory effects of ProS on VEGF-A-induced EC proliferation ( Figure 5A) and MAPK-Erk1/2 ( Figure 5B-C) and Akt activation ( Figure 5D-E).…”
Section: Protein S Inhibits Angiogenesis 5077mentioning
confidence: 99%
“…Basement membrane matrix (Matrigel) was purchased from BD Biosciences Discovery Labware. NSC87877 SHP 1/2 inhibitor 25 was from Tocris Bioscience. Recombinant human endostatin was from Biopur.…”
Section: Methodsmentioning
confidence: 99%
“…Inhibition of Shp2 enzymatic activity by overexpression of catalytically inactive Shp2 mutant did not destabilize p210 but enhanced serum starvation-induced apoptosis, suggesting that Shp2 also plays an important role in downstream signaling of the p210 kinase [5]. Interestingly, 8-hydroxy-7-(6-sulfonaphthalen-2-yl) diazenyl-quinoline-5-sulfonic acid (NSC-87877) has been identified as a small molecule with a potent inhibition effect on Shp2 protein-tyrosine phosphatase [10]. NSC-87877 binds to the catalytic cleft of Shp2 and is selective for Shp2 over other protein-tyrosine phosphatases without a detectable off-target effect [10].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Interestingly, 8-hydroxy-7-(6-sulfonaphthalen-2-yl) diazenyl-quinoline-5-sulfonic acid (NSC-87877) has been identified as a small molecule with a potent inhibition effect on Shp2 protein-tyrosine phosphatase [10]. NSC-87877 binds to the catalytic cleft of Shp2 and is selective for Shp2 over other protein-tyrosine phosphatases without a detectable off-target effect [10].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%